Identification and Situation Analysis of Historical Drought-Flood Abrupt Alternation in Jiulong River Basin in Fujian - SUN Haoyan; WANG Lihui; TANG Ping; XU Pu; JIANG Yong; YU Zhiming; ZOU Qingshui (Renmin Zhujiang)
To improve the scheduling plan for extreme hydrological events and drought-flood abrupt alternation in Jiulong River Basin,according to the historical observation data of the basin,this paper adopts the short-cycle drought-flood abrupt alternation index (SDFAI) and standard deviation method to identify and analyze the historical typical years of drought-flood abrupt alternation in Jiulong River Basin.The results are as follows:① From 1952 to 2021,the typical years of drought-flood abrupt alternation in this basin are evenly distributed with a total of 11 years,and the typical years of drought-flood abrupt alternation in the last ten years are 2016 and 2020;② The probability characteristics of drought-flood abrupt alternation in Jiulong River Basin in the four seasons are shown.In the case of droughts,the alternation probability from droughts to floods is less than that of continuous droughts.In the case of floods,the alternation probability from floods to droughts is greater than that of continuous floods;③ The hydrological situations of 1987,1995,and 2016 in the basin are analyzed,with the three years being the historical typical years of drought-flood abrupt alternation.Meanwhile,rainfalls and evaporation in typical years are compared with those in the whole year to obtain their monthly variation and then provide data support for formulating emergency scheduling schemes of drought-flood abrupt alternation.